Test-retest, intra- and inter-rater reliability of the reactive balance test: a neurocognitive functional test to evaluate adaptability within injury risk profiling - Tassignon, B.; Verschueren, J.; Wachter, J.; Maricot, A.; Pauw, K.; Verhagen, E.; Meeusen, R. (British Journal of Sports Medicine, 2021)
Background Balance tests are often selected to screen for injury risk, but only evaluate pre-planned movements. Recently, adaptability was put forward as a key driver in injury prevention. Adaptability is defined as athletes` ability to adequately adapt their responses under a comprehensive variety of conditions. The reactive balance test (RBT) is designed as a neurocognitive functional test that integrates environmental perception and decision-making to evaluate adaptability while maintaining unilateral balance.